2010
DOI: 10.1080/13557851003624273
|View full text |Cite
|
Sign up to set email alerts
|

‘Fasting and prayer don't concern the doctors … they don't even know what it is': communication, decision-making and perceived social relations of Pakistani Muslim patients with long-term illnesses

Abstract: Introduction With the introduction of highly active antiretroviral therapy the Hepatitis C virus (HCV) infection has became a primary health problem among individuals suffering from HIV/AIDS in Puerto Rico, principally those who are injecting drug users (IDUs). A multimedia educational intervention, based on the Health Beliefs Model and Social Cognitive Theory was developed and implemented to reduce HCV associated risk behaviors among IDUs. Methods A pre- and post- intervention study evaluated the knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…It is worth noting that one study reported no differences in attendance levels by language competency and has drawn attention to the fact that availability of translator services and advocacy for immigrant communities can help to ensure that there is no disparity in the delivery of services in this respect. 121 Second, higher levels of mistrust and lower degrees of therapeutic alliance or engagement with services have been noted for minority ethnic patients across several studies (see, for example, Mir and Sheikh 185 ).…”
Section: Explanations and Implications For Remindersmentioning
confidence: 99%
“…It is worth noting that one study reported no differences in attendance levels by language competency and has drawn attention to the fact that availability of translator services and advocacy for immigrant communities can help to ensure that there is no disparity in the delivery of services in this respect. 121 Second, higher levels of mistrust and lower degrees of therapeutic alliance or engagement with services have been noted for minority ethnic patients across several studies (see, for example, Mir and Sheikh 185 ).…”
Section: Explanations and Implications For Remindersmentioning
confidence: 99%
“…Culturally insensitive recommendations were ineffective, in that, directing patients peremptorily not to fast did not appear to deflect vulnerable patients from still undertaking the fast [42]. Generally, patients may choose to ignore HCP advice, especially if they feel the HCP is not culturally attuned to their decisions [42, 46, 47]. In the case of Ramadan fasting, where religious beliefs strongly motivate patients to fast, HCPs (physicians and pharmacists) and religious sources, such as imams (Muslim religious priests), may need to collaborate as important sources of knowledge about fasting and medication use for patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, understandable that healthcare staff make cognitive economies to simplify the complex work of healthcare practice. However, it also perpetuates a service in which healthcare professionals often remain ill-equipped to serve the needs of their ethnically diverse patient populations (Mir and Sheikh, 2010). Aronson et al (2013) explicitly link stereotyping to discrimination, health inequalities and poor health for those who are the targets of stereotypes, often those from minority ethnic groups.…”
Section: Implications For Practicementioning
confidence: 99%